2008
DOI: 10.1115/1.2976802
|View full text |Cite
|
Sign up to set email alerts
|

MG-IVT: An Infinitely Variable Transmission With Optimal Power Flows

Abstract: The infinitely variable transmissions (IVTs) allow the transmission ratio to vary with continuity, offering the possibility of also reaching zero values for the transmission ratio and the motion inversion. In this paper an original infinitely variable transmission system is described (MG-IVT). MG-IVT is made up of the coupling of a continuously variable transmission, a planetary gear train, and two ordinary transmissions with a constant transmission ratio. By means of two frontal clutches, the MG-IVT is allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Considering Figure 7(a), equation (19) is valid but, in this case, P 3 , which has the same value in the ideal system (P 3 id ) and in the real system (P 3 re ), is the input power of the ECVT. The power loss in the ECVT of the real ECVT eq can be expressed as a function of the power P 3 re (Figure 11) according to…”
Section: Compound Split In Direct Operation With Type III Power Flowmentioning
confidence: 96%
“…Considering Figure 7(a), equation (19) is valid but, in this case, P 3 , which has the same value in the ideal system (P 3 id ) and in the real system (P 3 re ), is the input power of the ECVT. The power loss in the ECVT of the real ECVT eq can be expressed as a function of the power P 3 re (Figure 11) according to…”
Section: Compound Split In Direct Operation With Type III Power Flowmentioning
confidence: 96%
“…In past research various power split devices were theoretically analyzed with focus on efficiency [21][22][23] and in some cases they were experimentally implemented and assessed on vehicles. For example, [24,25] experimentally verified some power split configurations on a test rig, also adopted for the characterization of particular operating conditions, like that of neutral gear in [26], and the evaluation of possible novel transmission layouts in [27]. In HEVs and BEVs with IVTs, during brake regeneration the transmission works in reverse mode, with a lower efficiency than in direct mode [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, it has been demonstrated that there is not any energy convenience when using shunted architectures with respect to, for instance, one toroidal CVT, because the enlargement of the ratio spread is counterbalanced by the average lower efficiency of the transmission [20,21]. In order to improve their efficiency performance, multiple mode devices could be used [22], but these devices have drawbacks in terms of size, weight and cost.…”
Section: Introductionmentioning
confidence: 99%